Comparison of mirror therapy and constraint-induced movement therapy on motor recovery and functional outcomes in post-stroke patients - Ogirahma; Husnul Mubarak; Sylvia Evelyn Aritonang; Andi Alfian Zainuddin; Anshory Sahlan; Melda Warliani (Physical Therapy Journal of Indonesia, 2026)
Background: Mirror therapy (MT) and constraint-induced movement therapy (CIMT) are rehabilitative techniques for improving upper limb function after stroke; however, direct comparisons of their effectiveness are limited. This study aimed to evaluate and compare the effects of MT and CIMT on upper limb recovery in stroke patients. Methods: A randomized controlled trial of 30 post-stroke patients was undertaken from June to September 2023. Participants were randomly assigned to either the MT or CIMT groups. The primary objective was the Fugl-Meyer assessment for upper extremities (FMA-UE), whereas the secondary outcomes were surface electromyography biofeedback (sEMG-B) and the box and block test (BBT). Results: CIMT significantly improved FMA-UE and BBT scores (p < 0.001), along with sEMG measurements of the middle, anterior, and posterior deltoid, biceps, triceps, wrist extensors, and wrist flexors (p < 0.001). MT also led to significant improvements in FMA-UE, BBT, and sEMG (all p < 0.001). Intergroup comparisons showed greater BBT score gains with CIMT (11) than MT (10), while differences in FMA-UE and sEMG were not significant. Conclusion: Both CIMT and MT enhance upper limb motor function in stroke patients, whereas CIMT results in higher increases in hand dexterity.